Identification, characterization and utilization of unigene derived microsatellite markers in tea (Camellia sinensis L.) - Mohapatra Trilochan; Negi Rinu; Bhardwaj Pankaj; Sharma Ram; Ahuja Paramvir (BMC Plant Biology, 2009)
Abstract Background Despite great advances in genomic technology observed in several crop species, the availability of molecular tools such as microsatellite markers has been limited in tea (Camellia sinensis L.). The development of microsatellite markers will have a major impact on genetic analysis, gene mapping and marker assisted breeding. Unigene derived microsatellite (UGMS) markers identified from publicly available sequence database have the advantage of assaying variation in the expressed component of the genome with unique identity and position. Therefore, they can serve as efficient and cost effective alternative markers in such species. Results Considering the multiple advantages of UGMS markers, 1,223 unigenes were predicted from 2,181 expressed sequence tags (ESTs) of tea (Camellia sinensis L.). A total of 109 (8.9%) unigenes containing 120 SSRs were identified. SSR abundance was one in every 3.55 kb of EST sequences. The microsatellites mainly comprised of di (50.8%), tri (30.8%), tetra (6.6%), penta (7.5%) and few hexa (4.1%) nucleotide repeats. Among the dinucleotide repeats, (GA)n.(TC)n were most abundant (83.6%). Ninety six primer pairs could be designed form 83.5% of SSR containing unigenes. Of these, 61 (63.5%) primer pairs were experimentally validated and used to investigate the genetic diversity among the 34 accessions of different Camellia spp. Fifty one primer pairs (83.6%) were successfully cross transferred to the related species at various levels. Functional annotation of the unigenes containing SSRs was done through gene ontology (GO) characterization. Thirty six (60%) of them revealed significant sequence similarity with the known/putative proteins of Arabidopsis thaliana. Polymorphism information content (PIC) ranged from 0.018 to 0.972 with a mean value of 0.497. The average heterozygosity expected (HE) and observed (Ho) obtained was 0.654 and 0.413 respectively, thereby suggesting highly heterogeneous nature of tea. Further, test for IAM and SMM models for the UGMS loci showed excess heterozygosity and did not show any bottleneck operating in the tea population. Conclusion UGMS markers identified and characterized in this study provided insight about the abundance and distribution of SSR in the expressed genome of C. sinensis. The identification and validation of 61 new UGMS markers will not only help in intra and inter specific genetic diversity assessment but also be enriching limited microsatellite markers resource in tea. Further, the use of these markers would reduce the cost and facilitate the gene mapping and marker-aided selection in tea. Since, 36 of these UGMS markers correspond to the Arabidopsis protein sequence data with known functions will offer the opportunity to investigate the consequences of SSR polymorphism on gene functions.